Waste Management Financing Model Through Utilization of Village Funds - Candrianto; Radna Ningsih2; Egy Juniardi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
This research is to create a model for the use of village funds for waste management, using the cost sharing method, namely the distribution of financing between the Padang Pariaman Regency APBD and the Village Fund as a transfer from the APBN. The survey method and literature for data collection in this study used village fund documents, district APBN funds, where respondents were asked to provide their responses to the management of village funds in waste management. Compilation of the concept of calculating waste management activities using activity based costing (ABC), dividing waste management financing through village fund financing is used to create a waste management financing model for Lubuk Alung sub-district to analyze the hypothetical relationship in the research model,